PEMODELAN ALGORITMA AHP DAN SMART PADA SISTEM REKOMENDASI PENERIMA BANTUAN RUMAH LAYAK HUNI DI DESA SIALAMBUE - Hasibuan, Bunga Lestari; Hasibuan, Muhammad Siddik; Rifki, Mhd.Ikhsan (UNIVERSITAS STEKOM, 2024)
The Livable Home Assistance Program is determined by the Government based on Government Regulation Number 12 of 2021, namely looking at the walls of the house, roof of the house, bathroom, floor of the house and floor area of ​​the house. Sialambue Village is one of the places that receives this program, because the conditions in Sialambue Village also make it possible to participate in this program. Therefore, data collection needs to be done more objectively to get accurate data collection results. So this research was carried out using the AHP and SMART algorithms by applying them to the Matlab application